Assessment of Development Results - Botswana - United Nations Development Programme (United Nations, 2009)
The UNDP Assessment of Development Results (ADR) in Botswana covers the period from 2003 to 2008 and includes the period of the current United Nations Development Assistance Framework (UNDAF) and UNDP country programme. It focuses on effectiveness, efficiency and sustainability, which refer to the assessment of development results and programme-level analysis, as well as on relevance, responsiveness, equity and partnerships, which relate to strategic positioning and analysis at a strategic level. The UN contribution to the development of Botswana has a long history. The current priority areas of action are: achieving the MDGs and reducing human poverty; energy and environment for sustainable development; and responding to HIV/AIDS.